THE EFFECT OF CUSTOMER PERCEPTION AND CUSOMER ATTITUDE TOWARDS MOBILE IN-APPLICATION ADVERTISING - Viclisika, Devinda; Arie, Fitty Valdi (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Advertising is very helpful for company to promote the product so they can reach more number of customers. Marketer have to be creative and following the trend to advertise their product and one of the advertising nowadays is in application on smartphone where in this era everyone are using a smartphone. This study aims to analyze the effect of customer perception and attitude towards mobile in-application advertising. This research is using quantitative research method and use multiple linear regression analysis. This research is using purposive sampling with 100 respondents as a sample. The result shows that customer perception and attitude have a positive relationship with mobile in-app advertising and significantly influenced mobile in-app advertising. So, it is better to the marketers to having some improvement in delivering the advertisement with the application of customer perceptions and attitudes elements.Keyword: advertising, mobile in-app, consumer behavior, customer perception, customer attitude